1979
DOI: 10.1016/0035-9203(79)90119-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunity of cholera in man: Relative role of antibacterial versus antitoxic immunity

Abstract: Purified cholera toxoid is antigenic when given enterally and orally. Purified toxoid fails to provide protection against experimental challenge. Clinical cholera confers formidable protection against homologous or heterologous rechallenge. Failure to culture vibrios from intestinal fluid or stool of re-challenge volunteers suggests that the predominant immune mechanism is antibacterial rather than antitoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 23 publications
6
125
0
Order By: Relevance
“…Nonseroconvertors had a significantly higher baseline GMT than did seroconvertors, and the higher the baseline titer, the lower the percentage of seroconversion (table 5). The final evidence comes from groups of North American volunteers who developed experimental cholera while serving as controls in vaccine efficacy studies and who were then rechallenged with pathogenic V. cholerae 0 I 2 months to 3 years later [10,[18][19][20]. These volunteers showed prominent rises in titer of serum vibriocidal antibody after their initial clinical cholera infection, which fell over 1-12 months to a level that was nevertheless above baseline [IOJ.…”
Section: Discussionmentioning
confidence: 99%
“…Nonseroconvertors had a significantly higher baseline GMT than did seroconvertors, and the higher the baseline titer, the lower the percentage of seroconversion (table 5). The final evidence comes from groups of North American volunteers who developed experimental cholera while serving as controls in vaccine efficacy studies and who were then rechallenged with pathogenic V. cholerae 0 I 2 months to 3 years later [10,[18][19][20]. These volunteers showed prominent rises in titer of serum vibriocidal antibody after their initial clinical cholera infection, which fell over 1-12 months to a level that was nevertheless above baseline [IOJ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies that have taken place indicate that serotype crossimmunity is almost complete (Levine 1978;Levine et al 1979). Additional patient studies show that a significant rise in vibriocidal antibodies to the heterologous serotype occurs in approximately 90% of infections ), further supporting a high level of cross-immunity, since vibriocidal levels are indicative of protection against cholera infection (Mosley 1969).…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Examination of convalescent cholera patients shows that both antibacterial and antitoxic responses are stimulated (Majumdar et al, 1981). Levine et al (1979) has demonstrated the relative importance of anti bacterial immunity in protection against cholera and, although this is believed to be mediated largely through the lipopolysaccharide (LPS) component of V. cholerae (Holmgren and Svennerholm, 1977;Chitnis et al, 1982;Dasgupta and Ghose, 1988), Attridge and Rowley (1983) have suggested that non-LPS antigens may also be involved in protection.…”
Section: Introductionmentioning
confidence: 99%